2020
DOI: 10.1017/ice.2020.26
|View full text |Cite
|
Sign up to set email alerts
|

Statewide surveillance of carbapenemase-producing carbapenem-resistant Escherichia coli and Klebsiella species in Washington state, October 2012–December 2017

Abstract: Background:Carbapenem-resistant Enterobacterales (CRE) are common causes of healthcare-associated infections and are often multidrug resistant with limited therapeutic options. Additionally, CRE can spread within and between healthcare facilities, amplifying potential harms.Objective:To better understand the burden, risk factors, and source of acquisition of carbapenemase genes in clinical Escherichia coli and Klebsiella spp isolates from patients in Washington to guide prevention efforts.Design:Multicenter pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Studies that do investigate this have shown that meat, particularly poultry, may be a source of E. coli infections in humans [17][18][19]. In Washington State, research has separately reported the presence of antimicrobial-resistant E. coli in the Salish Sea ecosystem [5] and in outpatient clinical samples isolated from Washington State Public Health Laboratories [11,20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies that do investigate this have shown that meat, particularly poultry, may be a source of E. coli infections in humans [17][18][19]. In Washington State, research has separately reported the presence of antimicrobial-resistant E. coli in the Salish Sea ecosystem [5] and in outpatient clinical samples isolated from Washington State Public Health Laboratories [11,20].…”
Section: Introductionmentioning
confidence: 99%